HOW THE CHURCH UNDER PIUS XII ADDRESSED DECOLONIZATION - Sergio, Marialuisa-Lucia, 1974- ([S.l.])
1 online resource
Keywords: By paying attention to Algerian Independence, this book reconstructs the action of the Catholic Church regarding the issues of the spread of Islam in colonies, to Arab nationalism, Marxist propaganda in non-European countries, and the effects of the Algerian crisis upon the French political system. The complex relations between the Holy See and France, as well as those between the Vatican and the Episcopates and clergy of the overseas territories, are vital aspects of decolonisation, a topic which, to date, has been overlooked by historiography because of the impossibility of accessing documents relating to the pontificate of Pius XII (1939-1958) held in the Vatican archives. The opening in March 2020 of the archives of Pius XII, the Pope who had succeeded in imposing the strategic role of the Holy See upon the international scene, has made a vast amount of unpublished documentary material available to scholars. This book is useful for all students and scholars interested in the Cold War, the history of contemporary Europe, the history of the Church, postcolonial studies, and religious phenomenon in post-World War II Europe.